PELAYANAN ADMINISTRASI GURU PAI PADA LEMBAGA PENDIDIKAN MELALUI APLIKASI SIAGA DI KABUPATEN KUTAI TIMUR - Poppy Putri Kusumaning Ayu (STAI Sangatta Kutai Timur, 2022)
Globalization makes the use of technology in all fields very much needed. Technology is not only in the form of physical tools but in the form of software, one of which is the application of information systems and administration of Islamic education teachers (SIAGA Pendis). In 2019 the Ministry of Religion through the Directorate of Islamic Religious Education published an application called SIAGA. With this application, the Ministry of Religion provides easy administrative services, especially for PAI teachers who are in public schools. Based on this, researchers are interested in knowing how the administrative services of PAI teachers at public education institutions through the SIAGA application in East Kutai Regency. The research was conducted using a qualitative approach with data collection from observations, interviews, and documentation.Furthermore, the data was analyzed using interactive analysis, namely by condensing the data, presenting the data, and ending with drawing conclusions. Based on the results of the analysis, it can be concluded that administrative services through the SIAGA application are registration and data collection of Islamic Religious Education teachers, recruiting teachers to conduct Teacher Professional Education (PPG), validating teacher data, and opening teacher professional allowances. All of them automatically use the Religious Teacher Information and Administration System (SIAGA) application which is held by the operator in the Islamic Religious Education (PAIS) section of the Ministry of Religion of East Kutai Regency. Although there are still many obstacles, the Ministry of Religion always socializes the SIAGA application.